Development of Chloroplast Microsatellite Markers and Analysis of Chloroplast Diversity in Chinese Jujube (Ziziphus jujuba Mill.) and Wild Jujube (Ziziphus acidojujuba Mill.) - Huang, Jian (PLoS One, 2015)
Ziziphus is an important genus within the family Rhamnaceae. This genus includes several important fruit tree species that are widely planted in China and India, such as the Chinese jujube (Ziziphus jujuba Mill.), the wild jujube (Z. acidojujuba), and the Indian jujube (Z. mauritiana). However, information about their domestication based on the chlorotype diversity of Chinese jujube population is lacking. In this study, chloroplast microsatellite (cpSSR) markers were developed and used to investigate the genetic relationships between and domestication of jujube cultivars and wild jujube populations. Primer sets flanking each of the 46 cpSSR loci in non-coding regions of the chloroplast genome sequence of Z. jujuba Mill. cv. ‘Junzao’ were designed. In total, 10 markers showed polymorphisms from 15 samples (9 jujube cultivars and 6 wild jujube individuals), of which 8 loci were due to variations in the number of mononucleotide (A/T) repeats and 2 were due to indels. Six cpSSR markers were used in further analyses of 81 additional samples (63 jujube cultivars, 17 wild jujube samples, and 1 Indian jujube). Using these cpSSR markers, the number of alleles per locus ranged from two to four. In general, the Shannon Index (I) for each cpSSR ranged from 0.159 to 0.1747, and the diversity indices (h) and uh were 0.061 to 0.435 and 0.062 to 0.439, respectively. Seven chlorotypes were found; the Indian jujube showed distinct chlorotypes, and both the Chinese and wild jujube had four chlorotypes and shared two chlorotypes. A dominant chlorotype (G) accounted for 53 of 72 jujube cultivars and 13 of 23 wild jujube individuals. All chlorotypes were highly localized along the Yellow River, from the mid- to the lower reaches, suggesting a wide origin of jujube. These cpSSR markers can be applied to population and evolution studies of Chinese jujube and wild jujube.